MicroRNA-663b enhances migration and invasion by targeting adenomatous polyposis coli 2 in colorectal carcinoma cells - Xiao, Fenqiang (Oncol Lett, 2020)
Colorectal carcinoma (CRC) is one of the leading causes of cancer-associated mortality worldwide. Dysregulation of microRNA (miR)-663b has been reported in a variety of diseases. However, the specific biological function of miR-663b in CRC requires further investigation. The aim of the present study was to elucidate the role and underlying molecular mechanism of action of miR-663b in CRC. Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) analysis and western blot analysis were employed to measure the expression of miR-663b at the RNA and protein level, respectively. Flow cytometry was used to detect cell apoptosis. Cell proliferation, migration and invasion were evaluated by the Cell Counting Kit-8, wound healing and Transwell assays, respectively. A dual-luciferase reporter assay was used to validate the potential target gene of miR-663b. The expression of miR-663b was identified to be markedly upregulated in CRC cells. Ectopic miR-663b expression promoted CRC cell proliferation, migration and invasion, and inhibited apoptosis. The dual-luciferase reporter assay identified adenomatous polyposis coli 2 (APC2) as a direct target of miR-663b in CRC cells. Further investigation indicated that miR-663b was involved in CRC cell invasion through the Wnt/β-catenin pathway. Therefore, overexpression of miR-663b was able to promote CRC cell proliferation, migration and invasion by regulating the Wnt/β-catenin pathway through targeting APC2, suggesting that miR-663b may be a useful target for the diagnosis and treatment of CRC.